Pengaruh Rekrutmen dan Pelatihan Terhadap Kinerja Tenaga Pengajar Pada Sanggar Anakku Sayang: The Influence of Recruitment and Training on the Performance of Teaching Staff at Sanggar Anakku Sayang - Firli Nafira; Susan Rachmawati (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to analyze the extent to which recruitment processes and training programs contribute to the performance of teaching staff at Sanggar Anakku Sayang. The research employed a quantitative approach using statistical analysis, with data collected through questionnaires. Respondents were selected using purposive sampling, involving 30 teaching staff who were actively teaching and had participated in IKM training. Data were obtained through Likert-scale questionnaires and analyzed using multiple linear regression analysis. The results indicate that recruitment has a significant effect on teaching staff performance, as shown by a t-value of 2,752, which is greater than the t-table value of 2,052, with a significance value of 0,010, contributing 33,6%. Training also has a significant effect, with a t-value of 2,364 exceeding the t-table value of 2,052 and a significance value of 0,026, contributing 29,5%. Simultaneously, recruitment and training have a significant effect on teaching staff performance, as indicated by an F-value of 11,024, which is greater than the Ftable value of 3,35, with a significance value of 0,000, and an adjusted R-square value of 40,9%. This study is expected to serve as a reference for sanggar management in improving recruitment processes and optimizing training implementation to enhance teaching staff performance